THE ROLE SOCIAL SUPPORT AND SPIRITUAL INTELLIGENCE ON STUDENTS’ MORALS IN ISLAMIC STUDENTS: PLS-SEM ANALYSIS - Nur Abdullah, Khafid; Diantoro, Fery (Abjadia : International Journal of Education, 2024)
This research aims to explore the role of Social Support in influencing the development of spiritual and moral intelligence in Islamic Studies. The research method used is quantitative, and research subject from students at the same relevant educational level. Research findings show that interactions with Social Support have a significant influence in shaping understanding of spiritual values and ethical behavior. Social Support act as socialization agents who facilitate the learning process and moral growth of students. The implications of this research highlight the importance of paying attention to social dynamics in curriculum design and learning program development to improve the spiritual and moral dimensions of religious education. Data collection was carried out using a questionnaire consisting of a Likert scale with 5 alternative answers 1 (strongly disagree) – 5 (strongly agree). PLS-SEM analysis was used to analyze data and test the conceptual model to searching data from existing variabels. The most dominant item representing the success of Spiritual Intelligence is emotional balance at 89.0%. The weakest construct is the construct of avoiding negative behavior at 71.10%. The path analysis test shows that the four variables have a data negative insignificant effect on Spiritual Intelligence and a data positive and significant effect on Spiritual Intelligence.